2009
DOI: 10.1590/s0073-47212009000200015
|View full text |Cite
|
Sign up to set email alerts
|

Composição e variabilidade espaço-temporal da meiofauna de uma praia arenosa na região amazônica (Ajuruteua, Pará)

Abstract: ABSTRACT. Composition and spatio-temporal variability of meiofauna community on a sandy beach in the Amazon region (Ajuruteua, Pará, Brazil). The present study investigates the spatio-temporal changes in the meiofauna community along the intertidal zone of Ajuruteua Beach, State of Pará, Brazil. Samples were collected during spring tides at different levels of the beach face every two months from April 2003 to February 2004. The material was sampled using a cylindrical corer (3.14 cm 2 ) and fixed with 5% sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
(23 reference statements)
0
6
0
1
Order By: Relevance
“…When compared with studies conducted in the Amazon region, where the size of the corer and the influence of rivers were similar, Caixa d'Água had values similar to those found by Rosa-Filho et al (2011) (500 -4000 ind./10cm 2 ) and Ataide et al (2014) (1710 -1832 ind./10cm 2 ), both conducted on the same beach or nearby. However, Caixa d'Água, which is an intermediate beach, had considerably higher density than Ajuruteua beach (also in the Amazon region and considered a dissipative beach), studied by Gomes and Rosa-Filho (2009), who found densities ranging from 553 to 674 ind./10cm 2 . Studying meiofauna of sandy beaches, McLachlan & Turner (1994) concluded that intermediate beaches provide suitable conditions for the success of interstitial fauna, which has higher densities and diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared with studies conducted in the Amazon region, where the size of the corer and the influence of rivers were similar, Caixa d'Água had values similar to those found by Rosa-Filho et al (2011) (500 -4000 ind./10cm 2 ) and Ataide et al (2014) (1710 -1832 ind./10cm 2 ), both conducted on the same beach or nearby. However, Caixa d'Água, which is an intermediate beach, had considerably higher density than Ajuruteua beach (also in the Amazon region and considered a dissipative beach), studied by Gomes and Rosa-Filho (2009), who found densities ranging from 553 to 674 ind./10cm 2 . Studying meiofauna of sandy beaches, McLachlan & Turner (1994) concluded that intermediate beaches provide suitable conditions for the success of interstitial fauna, which has higher densities and diversity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Nematoda are known to have higher abundance in the hottest period of the year in temperate regions (Coull, 1988) but, there is still no well-established pattern described to tropical regions. The few existing studies in these regions indicate rainfall as the major structuring factor of meiofauna and nematofauna (Pattnaik and Rao, 1990;Ingole and Parulekar, 1998;Gomes and Rosa-Filho, 2009;Venekey et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Albertelli et al, 1999;Rodríguez et al, 2001;Gheskiere et al, 2005;Kotwicki et al, 2005aKotwicki et al, , 2005bLeonardis et al, 2008;Gomes and Filho, 2009;Sandulli et al, 2010). Our average meiofauna abundances (1.5 Â 10 4 ind m…”
Section: Discussionmentioning
confidence: 67%
“…Gomes & Rosa Filho (2009) ao estudarem a composição e variabilidade espaço-temporal da meiofauna de umapraia arenosa na região amazônica (Ajuruteua, Pará) encontraram um total de oito grupos de organismos pertencentes a meiofauna, sendo estes: Turbellaria, Nematoda, Tardigrada, Polychaeta, Oligochaeta, Acarina, Copepoda Harpacticoida adultos e Copepoda Harpacticoida juvenis¸ o que contrasta com os resultados do presente estudo¸ que verificou a presença de somente 3 grupos (Nematoda, Copepoda e Polychaeta). Ambos os ecossistemas são praias amazônicas, entretantoa Praia do Goiabal apresenta características estuarinas, o que pode explicar a baixa diversidade de grupos de organismos.…”
Section: Discussionunclassified